HARNESSING ARTIFICIAL INTELLIGENCE IN MODERN MARKETING: STRATEGIES, BENEFITS, AND CHALLENGES - Zangana, Hewa; Omar , Marwan; Ali , Natheer Yaseen (tesco publisher, 2024)
In recent years, integrating Artificial Intelligence (AI) into marketing strategies has revolutionized the industry, providing businesses with unprecedented tools to analyze consumer behavior, personalize customer experiences, and optimize campaign performance. This paper explores the multifaceted impact of AI on modern marketing, highlighting key strategies businesses employ, the benefits realized through enhanced data analytics, automation, and customer engagement, as well as the challenges and ethical considerations accompanying AI adoption. By examining current trends and case studies, this study aims to provide a comprehensive understanding of how AI shapes the future of marketing, offering insights into best practices and potential pitfalls for marketers navigating this rapidly evolving landscape.